Pengaruh Kualitas Pelayanan,Kualitas Produk Dan Harga Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Sebagai Variabel Intervening (Studi Kasus Pada Pelanggan Toekuperabot Malang) - Khoirun Nisa’ Sri Agustin; Achmad Agus Priyono; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
This study aims to determine the quality of service, product quality and price to consumer loyalty through consumer satisfaction as an intervening variable. The sample in the study was 115 respondents. The data used are primary data using the distribution of questionnaires. The data analysis methods used are instrument tests: validity tests and reliability tests, normality tests, classical assumption tests: multicolonierity tests and heteroskedasticity tests, path analysis, hypothesis tests: partial tests and sobel tests.From the results of the study, the results were obtained that the quality of service to customer satisfaction had a significant effect. Product quality to consumer satisfaction has a significant effect. Price to consumer satisfaction has a significant effect. The quality of service to customer loyalty has a significant effect. Product quality to consumer loyalty has a significant effect. The price of consumer loyalty has no significant effect. Consumer satisfaction has a significant effect on consumer loyalty. Customer satisfaction mediates the quality of service to consumer loyalty. Consumer satisfaction mediates product quality against consumer loyalty. Consumer satisfaction mediates price to consumer loyalty. Keywords: Service Quality, Product Quality, Price, Customer Satisfaction, Consumer Loyalty, Intervening Variables.